1996
DOI: 10.1007/bf02628654
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of in vitro HIV infection by dialysable leucocyte extracts

Abstract: Dialysable Leucocyte Extract (DLE) is a low molecular weight dialysable material of disrupted peripheral human leucocytes with widespread effects on the immune system. We described the in vitro anti-HIV activity of DLE as well as its three chromatographic fractions (Fa, Fb and Fc). To determine the levels of inhibition on HIV replication by DLE we infected MT-4 cell cultures, using the Bru viral isolate at 0.05, 0.1, 0.5 and 1 m.o.i. Previously, MT-4 cells cultures were treated with DLE or fractions at non-tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In our assays, after pretreatment of the HeLa-CD4-LTR-β-gal cells and bDLE removal prior to viral challenge, protection against infection lasted 7 hours after bDLE was removed from the extracellular compartment (Figure 5). These results indicated that bDLE could induce long-term viral inhibition through cell protection, as well as modulate cell susceptibility to viral infection in vitro , in agreement with previously reported data on DLE obtained from human donors by molecular methods [9]. …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our assays, after pretreatment of the HeLa-CD4-LTR-β-gal cells and bDLE removal prior to viral challenge, protection against infection lasted 7 hours after bDLE was removed from the extracellular compartment (Figure 5). These results indicated that bDLE could induce long-term viral inhibition through cell protection, as well as modulate cell susceptibility to viral infection in vitro , in agreement with previously reported data on DLE obtained from human donors by molecular methods [9]. …”
Section: Discussionsupporting
confidence: 92%
“…Due to the DLE immunomodulatory properties discussed before, progression to AIDS in asymptomatic HIV-1 infected individuals treated with conventional anti-retrovirals, has shown a retarded progression to AIDS under adjuvant treatment with dialyzable leukocyte extract (DLE), demonstrated by lower incidences of opportunistic infections and improved cellular immunity [9,38,44]. DLE simultaneously shows anti-HIV activity [44,47,48], modulates different types of immune effectors ( e.g ., cytokines and transcription factors)[11,47,49] and restores leukocyte subsets in treated patients [16,29,35,37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations